Macromedia Flash 8 تخطيط الوسائط المتعددة التفاعلية في تعليم الاستماع باستخدام برنامج - Amira Juvi, Azka; Qusaiyen, Qusaiyen; Hayati, Salma (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2020)
Media is one of many ways to increase student’s interest in learning. The development of an innovative media can increase the student’s interest in learning and make the learning process more effective and fun. Furthermore, media may facilitate the teacher to presents the learning material. In this technology era, one of the technology-based learning media that can be developed is interactive multimedia. Interactive multimedia can be an interesting media in teaching because it contains many media such as picture, animation, audio, video, and text. This media takes ‘profession’ as the theme of Arabic language lesson for 2nd grade of junior high school student and it focused on listening skill. In learning Arabic as foreign language, learners have to master 4 language skills those are listening, speaking, reading and writing. Listening skill is the most important skill in learning Arabic language as the first skill in mastering other language skills. This article contains each stage of multimedia interactive design with 4 steps: (1) Preliminary research; (2) Development planning stage; (3) development stage; and (4) Product validation and revision stage. The purpose of this article is to design the interactive multimedia of learning Arabic language by using Macromedia Flash 8.